Hemorrhagic Lacrimation and Epistaxis in Acute Hemorrhagic Edema of Infancy - Shireen Mreish; Hossam Al-Tatari (Case Reports in Pediatrics)
Acute hemorrhagic edema of infancy is an uncommon benign cutaneous vasculitis. Despite its worrisome presentation, it carries good prognosis with rarely reported systemic involvement. Management of these cases has been an area of debate with majority of physicians adopting conservative modalities. We report a case that presented with classic triad of rash, low grade fever, and peripheral edema along with two rarely reported manifestations in literature: hemorrhagic lacrimation and epistaxis.